Ledakan Populasi Jenis Respo, Filicaulis bleekeri, di Sentra Produksi Sayur Rejang Lebong, Bengkulu - Dwinardi Apriyanto; B. Toha; I. Manti (Universitas Gadjah Mada, 2003)
During the last two years a slug species, Filicaulis bleekeri (Keferst.), has become important pest of some vegetable crops in vegetable production central Rejang Lebong,Bengkulu. This pest is called